Cu0-Functionalized, ZIF-8-Derived, Nitrogen-Doped Carbon Composites for Efficient Iodine Elimination in Solution - Jiuyu Chen; Chensheng Gao; Jingwen Chen; Fei Liu; Zhiwen Liu (Nanomaterials)
The development of copper-based materials with a high efficiency and low cost is desirable for use in iodine (I2) remediation. Herein, Cu0-nanoparticles-functionalized, ZIF-8 (Zeolite Imidazole Framework-8)-derived, nitrogen-doped carbon composites (Cu@Zn-NC) were synthesized by ball milling and pyrolysis processes. The as-prepared composites were characterized using SEM, BET, XRD, XPS, and FT-IR analyses. The results showed that the morphology of ZIF-8 changed from a leaf-like structure into an irregular structure after the introduction of a copper salt and carbonization. The copper in the pyrolysis samples was mainly in the form of Cu0 particles. The presence of an appropriate amount of Cu0 particles could increase the specific surface area of Cu@Zn-NC. The subsequent batch adsorption results demonstrated that the as-fabricated composites showed high I2 adsorption amounts (1204.9 mg/g) and relatively fast dynamics in an iodine–cyclohexane solution when the Cu content was 30% and the pyrolysis temperature was 600 °C, outperforming the other Cu-based materials. The isothermal adsorption followed both Langmuir and Dubinin–Radushkevich isotherm models, while the kinetics of I2 adsorption followed a pseudo-second-order kinetic model. The activation energy (Eα) of the adsorbent was determined to be 47.2 kJ/mol, according to the Arrhenius equation. According to the experimental and DFT analyses, I2-Zn interactions and I2-Cu0 chemisorption jointly promoted the elimination of iodine. In general, this study provided an operative adsorbent for the highly effective capture of iodine in solution, which might be worth applying on a large scale.